Light emission enhancement from ZnO nanostructured films grown on Gr/SiC substrates. (April 2016) - Khranovskyy, V.; Shtepliuk, I.; Ivanov, I.G.; Tsiaoussis, I.; Yakimova, R.
Abstract: We report on the application of a single layer graphene substrates for the growth of polycrystalline ZnO films with advanced light emission properties. Unusually high ultraviolet (UV) and visible (VIS) photoluminesce was observed from the ZnO/Gr/SiC structures in comparison to identical samples without graphene. The photoluminescence intensity depends non-monotonically on the films thickness, reaching its maximum for 150 nm thick films. The phenomena observed is explained as due to the dual graphene role: i) the dangling bond free substrate, providing growth of relaxed thin ZnO layers ii) a back reflector active mirror of the Fabry-Perot cavity that is formed. The reported results demonstrate the potential of two-dimensional carbon materials integration with light emitting wide band gap semiconductors and can be of practical importance for the design of future optoelectronic devices.